2019
DOI: 10.1101/746305
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complex symbiont-pathogen interactions inhibit intestinal repair

Abstract: SUMMARYPathogen-mediated damage to the intestinal epithelium activates compensatory growth and differentiation repair programs in progenitor cells. Accelerated progenitor growth replenishes damaged tissue and maintains barrier integrity. Despite the importance of epithelial renewal to intestinal homeostasis, we know little about the effects of pathogen-commensal interactions on progenitor growth. We found that the enteric pathogen Vibrio cholerae, blocks critical growth and differentiation pathways in Drosophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
2
1
0
Order By: Relevance
“…More recently, we showed that the T6SS also affects epithelial renewal in infected flies. In agreement with previous work (139), we showed that V. cholerae causes extensive damage to the midgut epithelium, but fails to activate compensatory proliferation in basal progenitor cells (166). Removal of the T6SS diminishes epithelial damage, and restores renewal in infected midguts.…”
Section: Vibrio Cholerae and Isc Growthsupporting
confidence: 93%
“…More recently, we showed that the T6SS also affects epithelial renewal in infected flies. In agreement with previous work (139), we showed that V. cholerae causes extensive damage to the midgut epithelium, but fails to activate compensatory proliferation in basal progenitor cells (166). Removal of the T6SS diminishes epithelial damage, and restores renewal in infected midguts.…”
Section: Vibrio Cholerae and Isc Growthsupporting
confidence: 93%
“…Of note, similar to our study, flagellar genes were identified as important colonization determinants of one microbiome member Acetobacter fabarum (47), suggesting this may be a common feature for bacterial persistence in the fly gut. Our previous work and other reports have highlighted a role for the microbiota in modulating enteric infection by bacteria, yeast, and viruses (48)(49)(50)(51)(52). We observed that colonization with a single member of the microbiota, Lactiplantibacillus plantarum, is sufficient to reduce mortality associated with S. marcescens, P. aeruginosa (41) and P. entomophila (51).…”
Section: Discussionsupporting
confidence: 50%
“…The bacterial dynamics can be complex. In the Drosophila model, V. cholerae with a functional T6SS inhibited host intestinal repair only when three common fly commensals were present altogether, rather than individually (Fast et al, 2020). In infant mice, V. cholerae expressing T6SS were able to compete against commensal Escherichia coli, with the E. coli demonstrating a 300-fold drop in CFU count per small intestine homogenate when compared to the group infected with V. cholerae expressing a defective T6SS (Zhao et al, 2018).…”
Section: Vibrio Cholerae Resistance To Gut Microbiome Dynamicsmentioning
confidence: 99%